Studies on carboxylases. IX. - Enzymatic inhibition of pyruvic carboxylase by antibiotics of the glycidic group (Revista Española de Fisiología, 1956)
Continuing the study of enzymatic inhibition of pyruvic carboxylase by the therapeutically important antibiotics, the antibiotics streptomycin and dihydrostreptomycin, erythromycin, neomycin and carbomycin have been tested with the following results:1) Inhibition by cloranphenicol is irreversible with respect of the substrate, on the other hand, addition of cocarboxylase markedly reduces inhibition; addition of thiamine has not the same effect.2) Streptomycin. Very high concentrations (from 0.05 M) are needed to obtain appreciable inhibitions. At concentrations in which the organisms treated are usually encountered, it has no inhibitory action on pyruvic carboxylase.3) Dihydrostreptomycin. Its inhibitory action is much more marked than that of streptomycin. At equal concentrations, inhibition with dihydrostreptomycin is triple that with streptomycin.4) Cocarboxylase added to the System does not modify the inhibitory action of dihydrostreptomycin.5) Erythromycin is a strong inhibitor of pyruvic carboxylase. The substrate has no protective action on the enzyme. Theoretical treatment would suggest that the mechanism of inhibition can be the formation of enzyme-substrate-inhibitor complexes more than the action of inhibitor on the free enzyme.6) Framycetin produces has a inhibition power on piruvic carboxylase varing with substrate concentration.7) Neomycin. Inhibits moderately and the substrate has a marked protective action. A competition between the antibiotic and the enzyme for the substrate is suggerested, inhibition constant is 4.5x10—3 M.8) Carbomycyn, in the concentrations usually used, has no action on carboxylase.